Pengelolaan Resort Pattunuang Karaenta dalam Perspektif Etnoekologi di Kabupaten Maros - Shinta, Andi Lathifah Faisal (LaGeografia, 2018)
This research is aimed to find out 1) the way of society in adapting to Resort Pattunuang Karaenta 2) management form of Pattunuang Karaenta Resort at this time 3) management of Pattunuang Karaenta Resort area in ethnoekologi perspective. Informants come from Samangki Village and Labuaja Village using snowball sampling. Data obtained from observation, documentation and interview. The result of this research indicates that 1) the community can certainly be adapted to the environment that coexist with the nature of this in synchronized with existing theory and proven by the result of field 2) The arrangement of the area is an effort to realize the management of the area more effectively and efficiently include the preparation of zonation and work area arrangement. Zoning that has been established, periodically within three years time period is monitored and evaluated the effectiveness based on the existing zonation 3) people are still very dependent on natural products to support their basic needs, and how nature can be sustainably needed awareness and awareness of the community to protect the environment they.